Photonic spin Hall effect in symmetrical structure containing Dirac semimetal materials. (22nd September 2022) - Qi, Song; Da, Haixia; Yan, Xiaohong
Abstract: Three-dimensional Dirac semimetal (3DDS) has attracted wide attraction due to its adjustable thickness and Fermi energy. However, the performance of photonic spin Hall effect in the structures with 3DDS is still unknown. In this work, we establish a symmetrical structure composed of the periodic 3DDS and Si to study the dependence of spin shift on the thickness and Fermi energy of 3DDS. We find that the magnitude and the position of the spin shift can be controlled by either the thickness or Fermi energy of 3DDS, whose maximum positive and negative spin shifts can reach up to 11.57 λ and − 8.29 λ when the thickness of 3DDS, the Fermi energy, the repetition number of 3DDS and Si and the beam waist are 100 nm, 0.15   eV, 4 and 30 λ, respectively. The enhanced spin shift is excited by surface plasmon resonance and the response of r s / r p with the incident angle can explain when and why the spin shift peak (valley) appears. In addition, the control of the repetition number of (3DDS-Si) N and (Si-3DDS) N is an effective way to adjust the magnitude and the position of the spin shift peak (valley). The realization of large and tunable spin shift in the symmetrical structure containing Dirac semimetal shows its great potential in the application of sensors, switches and optoelectronic devices.